'Peasants are peasants': Prejudice against displaced villagers in newly-built urban neighbourhoods in China. (June 2021) - Du, Huimin; Song, Jing; Li, Si-ming
This article explores contemporary prejudice against displaced villagers in urban China, drawing on a project on urban sprawl in Yinchuan where rural villages are absorbed into the urban area. The research demonstrates that media discourses about chaiqian baofahu and suzhi that stigmatise displaced villagers are being actively reproduced in everyday life in newly built urban neighbourhoods. Urbanites' prejudice against displaced villagers can be viewed as, on the one hand, a result of the feelings of relative deprivation from unfavourable comparisons with displaced villagers, while on the other hand, a response to maintain a positive ingroup identity – in this case, an urban and 'civilised' way of life. The article then examines the effectiveness of contact as a means for reducing prejudice, and reveals that intergroup contact in urban neighbourhoods does not necessarily create mutual understanding and trust. The article highlights the structural causes of prejudice and concludes by arguing for social transformation to challenge and reduce prejudice.